Proposal of New Block Cipher Algorithm Depend on Public Key Algorithms (Al-Mansour Journal, 2022)
Data that can be read and understood without any special measures is called plaintext or cleartext. The method of disguising plaintext in such a way as to hide its substance is called encryption. Encrypting plaintex results in unreadable gibberish called ciphertext. use encryption to ensur that information is hidden from anyone for whom it is not intended, even those who can see the encrypted data. The process of reverting ciphertext to its original plaintext is called decryption. This paper present design and implementation of new block cipher algorithm . this algorithm building depend on multi technique to get more diffusion and confusion . algorithm contain of 14 round where input 256 bite and output 512 bite in each round . where each round have five processing to get more complexity also in this proposed used another technique that give to algorithm more complexity this technique is used ( algamal) as stage in algorithm ( stage five).
Keywords: Encryption; Decryption; IP; IP-1; Al-gamal Public key